Membentengi Generasi Muda dari Radikalisme melalui Pendidikan Non-Formal - Rofiudin, M. Rizal; Ishaq, Ishaq; Mukaffan, Mukaffan (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2025)
Radicalism is a term used among academics to refer to an ideology that contradicts the Indonesian national ideology, Pancasila. There are many factors behind the emergence of radicalism in Indonesia, and almost all of them stem from the inability of certain groups to accept differences within their surrounding environment. In terms of religion, radical groups can be identified by their perspective in interpreting religious teachings. This article aims to describe the prevention of radicalism in non-formal education through the role of *Rijalul Ansor*, a sub-organization of Nahdlatul Ulama (NU). The method employed is descriptive qualitative, with data collected through observation, interviews, and documentation. The research findings indicate that the function of non-formal education in countering radicalism includes: 1) Instilling Pancasila values through selapanan (monthly study sessions). 2) Promoting nationalism through tawasul (prayers of intercession) to national heroes. 3) Providing an understanding of peaceful and tolerant religion through the study of Risalah Aswaja by KH Hasyim Asy’ari. 4) Constructing Qur’anic perspectives on religious moderation. The implementation of these efforts is carried out through the study of Risalah Aswaja and Mujahadah Dzikrul Ghafilin held every Senin Pon (a Javanese calendar day).